Choosing an identity : a general model of preference and belief formation - Chai, Sun-Ki (Book collections on Project MUSE., 2001)
Annotation Social science research is fragmented by the widely differing and seemingly contradictory approaches used by the different disciplines of the social sciences to explain human action. Attempts at integrating different social science approaches to explain action have often been frustrated by the difficulty of incorporating cultural assumptions into rational choice theories without robbing them of their generality or making them too vague for predictions. Another problem has been the major disagreements among cultural theorists regarding the ways in which culture affects preferences and beliefs. This book provides a general model of preference and belief formation, addressing the largest unresolved issue in rational choice theories of action. It attempts to play a bridging role between these approaches by augmenting and modifying the main ideas of the "rational choice" model to make it more compatible with empirical findings in other fields. The resulting model is used to analyze three major unresolved issues in the developing world: the sources of a government's economic ideology, the origins of ethnic group boundaries, and the relationship between modernization and violence. Addressing theoretical problems that cut across numerous disciplines, this work will be of interest to a diversity of theoretically-minded scholars. Sun-Ki Chai is Assistant Professor of Sociology, University of Arizona